Diagnosis Miskonsepsi Siswa MAN Insan Cendekia Jambi Pada Materi Fluida Statis dan Fluida Dinamis: Diagnosis of Student Misconceptions MAN Insan Scholar Jambi on Static and Dynamic Fluid Material - Sekar Olivia Yenti; Maison Maison; Syaiful Syaiful (Universitas Jambi, 2021)
Students' efforts in studying physics often encounter obstacles due to the assumption that physics is a difficult subject to understand and teaching physics tends to be less interesting, causing misconceptions. This study aims to identify the misconceptions experienced by students in static fluid and dynamic fluid materials through four-tier (four-tier) diagnostics. This study uses a quantitative description method, with respondents as many as 30 students of class XI MIA MAN Insan Cendekia Jambi. The results showed that the average misconception experienced by students was classified in the low category because the percentage of correct answers for all levels obtained was 12.4% and the percentage of students' misconceptions for all levels was 2.0%. In addition to misconceptions, there are still some students who belong to the Lack of Knowledge category, which is 8.67% including false positives of 43.20% and false negatives of 40.27%. This can happen because students do not understand the concept or it could be because students are not serious about working on the questions given.